2023
DOI: 10.1037/met0000557
|View full text |Cite
|
Sign up to set email alerts
|

True and error analysis instead of test of correlated proportions: Can we save lexicographic semiorder models with error theory?

Abstract: This article criticizes conclusions drawn from the standard test of correlated proportions when the dependent measure contains error. It presents a tutorial on a new method of analysis based on the true and error (TE) theory. This method allows the investigator to separate measurement of error from substantive conclusions about the effects of the independent variable, but it requires replicated measures of the dependent variable. The method is illustrated with hypothetical examples and with empirical data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…A family of models known as 'TE' models have been developed in a series of papers to address the problem of distinguishing true violations from those that might be due to error (Birnbaum, 2004(Birnbaum, , 2008(Birnbaum, , 2010(Birnbaum, , 2013(Birnbaum, , 2023a(Birnbaum, , 2023bBirnbaum et al, 2016;Bahra, 2012a, 2012b;Birnbaum and Gutierrez, 2007;Birnbaum and Quispe-Torreblanca, 2018;Birnbaum and Schmidt, 2008;Birnbaum and Wan, 2020). Research using replicated designs analyzed by TE models concluded that most people satisfy transitivity of preference, but a minority of participants can be found who exhibit systematic deviations from transitivity in specially constructed designs (Birnbaum, 2023a;Birnbaum and Bahra, 2012b;Birnbaum and Diecidue, 2015;Birnbaum and Gutierrez, 2007).…”
Section: The Problem Of Response Variabilitymentioning
confidence: 99%
“…A family of models known as 'TE' models have been developed in a series of papers to address the problem of distinguishing true violations from those that might be due to error (Birnbaum, 2004(Birnbaum, , 2008(Birnbaum, , 2010(Birnbaum, , 2013(Birnbaum, , 2023a(Birnbaum, , 2023bBirnbaum et al, 2016;Bahra, 2012a, 2012b;Birnbaum and Gutierrez, 2007;Birnbaum and Quispe-Torreblanca, 2018;Birnbaum and Schmidt, 2008;Birnbaum and Wan, 2020). Research using replicated designs analyzed by TE models concluded that most people satisfy transitivity of preference, but a minority of participants can be found who exhibit systematic deviations from transitivity in specially constructed designs (Birnbaum, 2023a;Birnbaum and Bahra, 2012b;Birnbaum and Diecidue, 2015;Birnbaum and Gutierrez, 2007).…”
Section: The Problem Of Response Variabilitymentioning
confidence: 99%